Comparative analysis of domestic commercial air transport of routes, frequencies and airlines to and from the Bogotá International Airport from August 01 to 15, 2022 - Ribadeneira Páez , María Gracia; Jonathan Luis Cruz Pierard (Dominio de las Ciencias, 2023)
The objective of this study is to identify the market share of domestic commercial air transport by routes, frequencies and airlines from and to the International Airport El Dorado during a weekly period of time from August 1st to 15th, 2022. This has been achieved through a quantitative investigation with a descriptive type, which seeks to specify important characteristics of the phenomenon of study, in addition to defining variables and measuring concepts, in this case, the share of the domestic market. In addition, the process of obtaining results is reflected in the analysis of the exposed participation of the domestic market of the airlines that operate these routes in Colombia.